Virtual Reality-Based Game Learning on Animal Reproduction for Elementary School Level - Nugrahaningrum, Omega Widiarti; Sayekti, Ika Candra (Universitas Muhammadiyah Surakarta, 2023)
The transition from Industrial era 4.0 to Society era 5.0 brings significant changes to education in Indonesia. However, technology use in elementary schools is limited, particularly in biology education, which involves observational processes. To address this, researchers developed a virtual reality-based game for teaching animal reproduction at the elementary level. The research focuses on developing and validating the virtual reality-based game learning media, using the ADDIE model. Data was collected through observations, interviews, questionnaires, and validation. Experts validated the media, and practicality tests were conducted on 5 students at Elementary school 2 Gunungsari, Boyolali. The results showed a validity level of 77.3% and a practicality level of 79.99%, indicating that the virtual reality-based game can enhance students' understanding and provide an engaging learning experience.